Peran keluarga dalam pencegahan COVID-19: Edukasi komunikasi masyarakat melalui group counseling - Nur Hamim; Nafolion Nur Rahmat (Jurnal Dedikasi Masyarakat, 2022)
The community service initiative conducted in Kalibuntu Village, Kraksaan, Probolinggo Regency, aimed to enhance community understanding and involvement in combating the COVID-19 pandemic by imparting health education and promoting family communication. Society encountered challenges stemming from inadequate awareness regarding the significance of family communication amidst the pandemic and the detrimental effects of social isolation on mental and emotional well-being. The initiative sought to address these issues by fostering a deeper comprehension of family communication during crises and enhancing knowledge of COVID-19 prevention measures. The implementation methodology encompassed preparation, execution, and evaluation stages. Preparation involved liaising with the village, identifying participants, preparing materials, and extending invitations. Implementation featured health education sessions and group discussions led by students and supported by village healthcare professionals. Evaluations conducted pre- and post-activity gauged participants' knowledge enhancement and the active engagement of stakeholders. Results revealed a substantial improvement in participants' understanding of family communication and COVID-19 prevention measures. Active involvement from village cadres, healthcare professionals, and students significantly contributed to the program's success, as evidenced by the evaluation. Participant enthusiasm underscored the relevance and importance of health education and family communication in pandemic response efforts. Overall, the community service initiative effectively achieved its objective of enhancing community understanding and involvement in combating the COVID-19 pandemic in Kalibuntu Village. Positive participant evaluations, coupled with robust support from various stakeholders and the local government, lay a solid groundwork for the development of more impactful public health initiatives in the future.